Changes in Methane Emission and Community Composition of Methane-Cycling Microorganisms Along an Elevation Gradient in the Dongting Lake Floodplain, China - Yijie Ren; Lianlian Zhu; Zhengmiao Deng; Yonghong Xie; Chengyi Zhang; Fengjin Xiao; Xinsheng Chen; Feng Li; Yeai Zou; Rong Sheng; Xiaoyan Zhang; Xian Chen (Atmosphere, 2020)
Methane (CH4) emission and environmental controls of CH4-cycling microorganisms are unclear in inland floodplains. Here, we examined soil CH4 emissions and the community composition of CH4-cycling microorganisms under three vegetation types—mudflat (MF, no vegetation cover), Carex meadow (CM, mainly Carex brevicuspis), and reed land (RL, mainly Miscanthus sacchariflorus)—from water-adjacent areas to higher-elevation land in the Dongting Lake floodplain, China. The results showed that CH4 emission is the highest in CM, while significant absorption was observed in the RL site. The abundance ratio of methanogen/methanotroph was the highest in CM, intermediate in MF, and lowest in RL. The Methanosarcinaceae family represented the dominant methanogens in the three sampling sites (41.32–75.25%). The genus Methylocystis (60.85%, type II methanotrophs) was dominant in CM, while Methylobacter and Methylosarcina (type I methanotrophs) were the dominant genera in MF (51.00%) and RL (50.24%), respectively. Structural equation model analysis showed that methanogen and methanotroph abundance were affected by water table depth, soil water content, and pH indirectly through soil organic content, total nitrogen, microbial biomass carbon, and microbial biomass nitrogen. These results indicated that the Dongting Lake floodplain may change from a CH4 source to a CH4 sink with vegetation succession with an increase in elevation, and the methanogen/methanotroph ratio can be used as a proxy for CH4 emission in wetland soils. The continuous increase in reed area combined with the decrease in Carex meadow may mitigate CH4 emission and enhance the CH4 sink function during the non-flood season in the Dongting Lake floodplain.